Notes on Bryum medianum Mitt. (Bryaceae) collected from Tsum Valley, central Nepal - Gajurel, J. P.; Rai, S. K.; Pradhan, N.; Scheidegger, C. (Banko Janakari, 2018)
Not available. Banko Janakari A Journal of Forestry Information for Nepal Vol. 27, No. 2, 2017, Page: 51-52